Implementasi Metode Client Server pada Penerapan Aplikasi Simulasi Ujian Akhir - Alfiansyah Hasibuan; Erwin Dalimunthe (Jurnal Informatika Universitas Pamulang, 2020)
In the current era, where technology has become a necessity, not only in terms of information sources but also as a tool to process data. Client Server is a connectivity on the network that distinguishes computer functions whether as a client or server. This architecture makes a computer as a server or center in charge of providing services to other terminals (clients) connected to this network system. In this system, the design of the exam simulation by applying the client server method, where the computer used by students to answer questions is the client and the computer used by the lecturer to monitor and fill questions is a server. In solving problems that arise, an agency must have a system that can overcome these problems. The proposed system in overcoming problems is a computerized system to produce effective and efficient information, and to make reports more quickly and accurately. The exam simulation application designed is very helpful for lecturers to carry out and check exam results quickly and accurately.